Nickel(II) meso‐Hydroxyporphyrin Complexes Revisited: Palladium‐Catalysed Synthesis, Electronic Structures of Derived Oxy Radicals, and Oxidative Coupling to a Dioxoporphodimethene Dyad. Issue 10 (2nd February 2016) - Esdaile, Louisa J.; Rintoul, Llew; Goh, Mean See; Merahi, Khalissa; Parizel, Nathalie; Wellard, R. Mark; Choua, Sylvie; Arnold, Dennis P.
Abstract: We report the synthesis and characterisation of new examples of meso ‐hydroxynickel(II) porphyrins with 5, 15‐diphenyl and 10‐phenyl‐5, 15‐diphenyl/diaryl substitution. The OH group was introduced by using carbonate or hydroxide as nucleophile by using palladium/phosphine catalysis. The NiPor−OHs exist in solution in equilibrium with the corresponding oxy radicals NiPor−O . . The 15‐phenyl group stabilises the radicals, so that the 1 H NMR spectra of NiPor−OH are extremely broad due to chemical exchange with the paramagnetic species. The radical concentration for the diphenylporphyrin analogue is only 1 %, and its NMR line‐broadening was able to be studied by variable‐temperature NMR spectroscopy. The EPR signals of NiPor−O . are consistent with somewhat delocalised porphyrinyloxy radicals, and the spin distributions calculated by using density functional theory match the EPR and NMR spectroscopic observations. Nickel(II) meso ‐hydroxy‐10, 20‐diphenylporphyrin was oxidatively coupled to a dioxo‐terminated porphodimethene dyad, the strongly red‐shifted electronic spectrum of which was successfully modelled by using time‐dependent DFT calculations. Abstract : Radically different porphyrins : Nickel(II) complexes of meso‐ hydroxy‐15‐phenyl‐10, 20‐diarylporphyrins exist in solution in equilibrium with the corresponding oxy radicals (see figure), as shown by EPR spectra and the effects of addition of hydrazine on the NMR spectra. The analogous radicals without the 15‐phenyl substituent are much less stable. The spin distributions have been modelled by DFT calculations.